Effect of Fuel Injection Timing on Marine Diesel Engine Blended with Isoamyl Alcohol. Issue 1 (1st January 2023) - Lin, Hang; Huang, Zhaoxia; Huang, Jialiang; Li, Pinfang; Wang, Qiwei; Zhang, Feifei; Fan, Jinyu
Abstract: In order to study the problem that the pressure in the cylinder decreases significantly after diesel is mixed with isopentanol, which leads to the reduction of power performance, the software of AVL-FIRE is used for simulation, and the angle of start injection is adjusted to improve cylinder pressure. It turns out that in terms of combustion, The maximum burst pressure is reduced after mixing isoamyl alcohol. By increasing fuel injection timing, maximum burst pressure can rise to 87.8%-94.5% of the original engine respectively. The indicated power can be increased to 91.92%-95.62% of the original. In terms of emissions, after mixing, with the increase of fuel injection timing, NO does not change significantly, Soot shows a downward trend.